Galileo's surveying potential E5 pseudorange precision - Colomina, Ismael; Miranda, Christian; Pares, M. Eulälia; Andreotti, Marcus; Hill, Chris; Silva, Pedro F. da; Silva, Joao S.; Peres, Tiago; Monico, João F. Galera [UNESP]; Camargo, Paulo O.; Fernández, Antonio; Palomo, José Maria; et al. (My University, 2012)
New Galileo signals have great potential for pseudorange-based surveying and mapping in both optimal open-sky conditions and suboptimal under-canopy environments. This article reviews the main features of Galileo's E5 AItBO( and El (BOC signals, describes generation of realistic E5 and El pseudoranges with and without multipath sources, and presents anticipated horizontal positioning accuracy results, ranging from 4 centimeters (open-sky) to 14 centimeters (under-canopy) for E5/El.
Keywords: accuracy assessment; Galileo mission; positioning system; precision; signal processing; surveying